Communicating Gender Norms: A Discourse Analysis of "Not Your Barbie Girl" and "Barbie Girl" - Rokhmah, Desy Eva Laila; Betaubun, Martha; Purwaningsih, Yuni Ratna (Indonesian Journal of Science, Technology and Humanities, 2024)
This study uses discourse analysis to explore the portrayal of women in two iconic songs: Ava Max's "Not Your Barbie Girl" (2018) and Aqua's "Barbie Girl" (1997). The research highlights how they construct and convey particular social identities, roles, and ideologies by examining the language and discursive strategies used in these songs. The analysis reveals significant shifts in the representation of women over time, reflecting broader societal changes and evolving feminist discourses. This paper contributes to understanding how popular music shapes and reflects societal attitudes towards women, advocating for more inclusive and empowering representation in the media